Agronomic and Seed Quality Traits Dissected by Genome-Wide Association Mapping in Brassica napus - Körber, Niklas; Bus, Anja; Li, Jinquan; Parkin, Isobel A. P.; Wittkop, Benjamin; Snowdon, Rod J.; Stich, Benjamin (Frontiers in Plant Science, 2016)
In Brassica napus breeding, traits related to commercial success are of highest importance for plant breeders. However, such traits can only be assessed in an advanced developmental stage. % as well as require high experimental effort due to their quantitative inheritance and the importance of genotype*environment interaction. Molecular markers genetically linked to such traits have the potential to accelerate the breeding process of B. napus by marker-assisted selection. Therefore, the objectives of this study were to identify (i) genome regions associated with the examined agronomic and seed quality traits, (ii) the interrelationship of population structure and the detected associations, and (iii) candidate genes for the revealed associations. The diversity set used in this study consisted of 405 Brassica napus inbred lines which were genotyped using a 6K single nucleotide polymorphism (SNP) array and phenotyped for agronomic and seed quality traits in field trials. In a genome-wide association study, we detected a total of 112 associations between SNPs and the seed quality traits as well as 46 SNP-trait associations for the agronomic traits with a P-value < 1.28e-05 (Bonferroni correction of alpha=0.05) for the inbreds of the spring and winter trial. For the seed quality traits, a single SNP-sulphur concentration in seeds (SUL) association explained up to 67.3 % of the phenotypic variance, whereas for the agronomic traits, a single SNP-blossom color (BLC) association explained up to 30.2 % of the phenotypic variance. In a basic local alignment search tool (BLAST) search within a distance of 2.5 Mbp around these SNP-trait associations, 62 hits of potential candidate genes with a BLAST-score of > 100 and a sequence identity of > 70 % to A. thaliana or B. rapa could be found for the agronomic SNP-trait associations and 187 hits of potential candidate genes for the seed quality SNP-trait associations.